2022
DOI: 10.1080/2578983x.2021.1950466
|View full text |Cite
|
Sign up to set email alerts
|

Gendered feelings of unsafety and avoidance of local central areas in Finland 2001–2016

Abstract: There is a lack of knowledge about fear-of-crime-related place avoidance in Finland. International studies have examined different aspects of fear of crime and avoidance. However, examinations of the association between feelings of unsafety and place avoidance are rarer. This study takes on a less-researched perspective and examines the association between feelings of unsafety and avoidance of local central areas in Finland in 2001-2016. It conducts a gendered assessment of the association and distinguishes be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…It is uncertain what underlies this difference and whether it relates to methodological, social and/or cultural differences etc., although our finding seems to concur with earlier research which showed that women were more likely to have a high level of worry about crime than men ( Allen, 2006 ), which may be related to a range of factors including women's greater physical and social vulnerability and differences in socialisation ( Hale, 1996 ; Henderson & Bialeschki, 1993 ), and that women are more likely to engage in avoidance behaviours ( Hale, 1996 ). Indeed, in line with a number of studies that have highlighted the predominance of crime-related avoidance behaviours in women ( Kujala, 2022 ), it has been suggested that such constraints may become internalised and normalised with potentially detrimental consequences for some women ( Lorenc et al, 2012 ) – including possibly an increased risk of loneliness.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…It is uncertain what underlies this difference and whether it relates to methodological, social and/or cultural differences etc., although our finding seems to concur with earlier research which showed that women were more likely to have a high level of worry about crime than men ( Allen, 2006 ), which may be related to a range of factors including women's greater physical and social vulnerability and differences in socialisation ( Hale, 1996 ; Henderson & Bialeschki, 1993 ), and that women are more likely to engage in avoidance behaviours ( Hale, 1996 ). Indeed, in line with a number of studies that have highlighted the predominance of crime-related avoidance behaviours in women ( Kujala, 2022 ), it has been suggested that such constraints may become internalised and normalised with potentially detrimental consequences for some women ( Lorenc et al, 2012 ) – including possibly an increased risk of loneliness.…”
Section: Discussionmentioning
confidence: 85%
“…Indeed, this might help explain the finding that if older adults experience fear of crime, they suffer more than younger people ( Greve, 1998 ). In particular, research has highlighted the detrimental effects of fear and worry about crime on older adults' activity and mobility patterns ( Pain, 2000 ) including place avoidance ( Kujala, 2022 ) and limiting movement after dark ( Whitley & Prince, 2005 ). This might be important for loneliness among older adults in our study countries – especially in the context of other factors.…”
Section: Discussionmentioning
confidence: 99%